2011
DOI: 10.1002/adem.201000270
|View full text |Cite
|
Sign up to set email alerts
|

Macro‐ and Nanomechanical Properties and Strain Rate Sensitivity of Accumulative Roll Bonded and Equal Channel Angular Pressed Ultrafine‐Grained Materials

Abstract: Ultrafine-grained (UFG) metals produced by severe plastic deformation (SPD), i.e. equal channel angular pressing (ECAP) or accumulative roll bonding (ARB), exhibit outstanding mechanical properties. They show a high strength often paired with good ductility under monotonic loading and a strain rate sensitive behavior. [1] This is not only true for pure metals like aluminium of technical purity but also for other materials. [2][3][4][5][6] The enhanced strain rate sensitivity (SRS) is widely accepted to be a ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 26 publications
5
44
0
Order By: Relevance
“…The efficiency of ARB deformation would be more obvious if the ARB process was conducted at room temperature. Cherukuri et al [33] and Böhner et al [20] conducted ARB and ECAP deformation on aluminium alloys up to the same accumulative strain and found that ARB processed samples had higher strength, which is consistent with the results of the present work. The difference between the ARB and ECAP processed AA1050 can be explained by the different deformation modes.…”
Section: Comparison With Ecapsupporting
confidence: 91%
See 1 more Smart Citation
“…The efficiency of ARB deformation would be more obvious if the ARB process was conducted at room temperature. Cherukuri et al [33] and Böhner et al [20] conducted ARB and ECAP deformation on aluminium alloys up to the same accumulative strain and found that ARB processed samples had higher strength, which is consistent with the results of the present work. The difference between the ARB and ECAP processed AA1050 can be explained by the different deformation modes.…”
Section: Comparison With Ecapsupporting
confidence: 91%
“…A systematic study on the properties of the ARB processed commercial pure aluminium is still essential, and some aspects of the properties like the interfacial microstructure and its formation mechanism and effects have never been studied in detail. Böhner et al [20] studied the difference of commercial purity aluminium after ECAP and ARB to the same strain by the tensile test and nanoindentation and found that the material after ARB was stronger at the tensile test but weaker at the nanoindentation test. The difference in microstructure was not studied.…”
Section: Introductionmentioning
confidence: 99%
“…12). The estimated nanoindentation m-value for bulk ARB Al is in good accordance to values in literature from Schweitzer et al 40 and Böhner et al, 25 who found an m-value around 0.07 in UFG samples.…”
supporting
confidence: 90%
“…Further details on the ARB process and the materials properties can be found in Höppel et al 8 and Böhner et al 25 NC-Ni and UFG-Al cross sections were prepared for metallographic and nanoindentation examinations. The specimens were mounted in Technovit 4071 (Technovit, Heraeus-Kulzer, Germany) and acrylic resin Technovit 2000 LC, respectively, ground, polished with diamond down to 1 lm, and electrolytically polished.…”
Section: Experimental a Materials And Sample Preparationmentioning
confidence: 99%
“…It should be noted that the improved m value of 0.1 for the MMNC in the Al-Mg system after HPT and PDA is even higher than earlier reports where m values were estimated through nanoindentation testing of ~0.07 for a commercial purity Al after ECAP for 6-12 passes at RT [39][40][41][42] and after ARB for 8 cycles at RT [40] and ~0.035-0.050 for a ZK60 alloy after HPT for 2 turns at RT [43]. Thus, the MMNC after HPT followed by PDA demonstrates a significantly higher value of m compared with the initial materials when they are processed separately.…”
Section: The Improvement In Micro-mechanical Response By Pdamentioning
confidence: 58%